The killer collective - Eisler, Barry (Seattle : Thomas & Mercer, 2019)
When a joint FBI-Seattle Police investigation into an international child pornography ring gets too close to powerful enemies, sex-crimes detective Livia Lone becomes the target of a hit that barely goes awry, and suspects that the FBI itself was behind it.
Includes bibliographical references.
Keywords: Rain, John (Fictitious character) -- Fiction; Women detectives -- Fiction; Sex crimes -- Investigation -- Fiction; Assassins -- Fiction; Thrillers (Fiction); Political fiction